Longitudinal Morphological Changes in the Adenoids and Tonsils in Japanese School Children - Hiroshi Yamada (MDPI AG, 2021)
The adenoid (Ad) and tonsil (Ts), located in the upper airway, play an important role in immunological protection. These lymphoid tissues grow rapidly, reach a peak of growth at the age of 6–8 years, and decrease in their size thereafter. However, little information is available on the longitudinal growth patterns of Ad and Ts in the general population. This study aimed to evaluate the individual growth of Ad and Ts during childhood using lateral cephalograms taken longitudinally from the same individuals at the ages of 8–12 years. Our results showed that the cross-sectional areas of the Ad, nasopharynx (Np), and oropharynx (Op) significantly increased with age while small changes in the size of Ts were present throughout the study period. In addition, the values of Ad/Np and Ts/Op decreased significantly with age in the elementary school. Furthermore, there was a strong and significant correlation between the Ad/Np ratio and upper airway resistance, indicating the narrowest distance in the upper airway. In conclusion, the airway occupation in Np and Op increased with age due to the increase in the sizes of Np and Op but not the decrease in the sizes of Ad and Ts.